Physical Asset Management - Hastings, Nicholas A. J.; SpringerLink (Online service) (London : Springer London, 2010)
Physical asset management is the management of fixed or non-current assets such as equipment and plant. Physical Asset Management presents a systematic approach to the management of these assets from concept to disposal. Historically, asset management has not been seen as a specific professional activity, but now perceptions are changing. Many organizations are introducing senior positions in asset management, and universities are introducing courses in asset management at graduate and advanced undergraduate level. The broad reach of this book means that it will be applicable to professionals and future professionals across a wide variety of industries, ranging from manufacturing and distribution, to local government. The general principles of physical asset management are discussed in a manner which makes them accessible to a wide audience, and covers all stages of the asset management process, including: initial business appraisal; identification of fixed asset needs; financial evaluation; logistic support analysis; life cycle costing; maintenance strategy; outsourcing; cost-benefit analysis; disposal; and renewal. Physical Asset Management addresses the needs of existing and potential asset managers, and provides an introduction to asset management for professionals in related disciplines, such as finance. The book provides both an introduction and a convenient reference work, covering all the main areas of physical asset management.
to Asset Management -- The Asset Management Function -- From Concept to Project Approval -- Developing a Business Case -- Implementing Development Plans -- Management of In-Service Assets -- Asset Continuity Planning -- Capital Planning and Budget -- Discounted Cash Flow and Asset Decisions -- Profit, Depreciation and Tax -- Asset Investment Criteria -- Cost-Benefit Analysis -- Risk Analysis and Risk Management -- Logistic Support -- Life Cycle Costing -- Equipment Replacement Decisions -- Outsourcing -- Know Your Assets -- Asset Management Information Systems -- Maintenance Organization and Budget -- Reliability, Availability, Maintainability -- Inventory -- Key Performance Indicators -- PAS-55 Asset Management Specification.
Keywords: Engineering; Engineering economy; System safety; Banks and banking; Technology; Engineering; Quality Control, Reliability, Safety and Risk; Engineering Economics, Organization, Logistics, Marketing; Technology Management; Finance /Banking.